Energy spectra of accelerated electrons of chain relativistic electron bunches at excitation of wakefield in dielectric resonator - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2015)
The energy spectra of a long sequence of relativistic electron bunches at the output of the dielectric resonator taking into account initial energy spread of the relativistic electron bunches are investigated. It is considered also the finite value of the Q-factor of the dielectric cavity.